An elective single cleavage embryo transfer strategy to minimize twin live birth rate based on a prediction model from double cleavage embryos transfer patients. (3rd May 2022) - Huang, Xiaomin; Liu, Rong; Shen, Wenjuan; Cai, Yunni; Ding, Min; Sun, Haixiang; Zhou, Jianjun
Abstract: Objective: To minimize twin birth rate by establishing an elective single cleavage embryo transfer strategy based on a twin live birth prediction model from fresh double cleavage embryos transfer (cleavage DET) patients. Methods: A total of 2478 patients underwent fresh cleavage DET in Nanjing Tower Hospital were enrolled to establish the twin live birth prediction model by logistic regression analysis and the cutoff value was calculated by ROC curve. Another 300 fresh cleavage DET patients and 550 cleavage single-embryo transfer (SET) patients were selected to testify the sensitivity, specificity and usefulness of this model. Results: The twin live birth probability (TLBP) = e X /( e X + 1), e is a natural logarithm, X = −1.763 – (0.319 × female age) + (0.329 × endometrial thickness) + (0.282 × the number of transferred top embryos) – (0.314 × previous transfer times), and the cutoff value of TLBP was 24.2%. The sensitivity of this model for predicting twin live birth was 75.6%, while the specificity was 52.5% in the external validation of 300 DET patients. Furthermore, the validation of 550 SET patients showed that the live birth rate of TLBP value positive patients was significantly higher than that in negative patients (54.3% vs. 35.5%, p < .001). When adopted an elective single cleavage embryo transfer strategy, the patients with a positive TLBP value choose SET, while still undergo DET who with a negative TLBP value, the live birth rate would maintain as 56.7%; however, the twin birth rate would significantly decline to 7.4%. Conclusion: Female age, endometrial thickness, the number of transferred top embryos and previous embryo transfer times were critical variables for the twin live birth prediction model. An elective single cleavage embryo transfer strategy according to this model can maintain the relatively high live birth rate, meanwhile get the acceptable low twin birth rate.